Hepatic mitochondrial DNA/Toll‐like receptor 9/MicroRNA‐223 forms a negative feedback loop to limit neutrophil overactivation and acetaminophen hepatotoxicity in mice. Issue 1 (22nd May 2017) - He, Yong; Feng, Dechun; Li, Man; Gao, Yanhang; Ramirez, Teresa; Cao, Haixia; Kim, Seung‐Jin; Yang, Yang; Cai, Yan; Ju, Cynthia; Wang, Hua; Li, Jun; et al.
Abstract : Acetaminophen (APAP) overdose is a leading cause of acute liver failure worldwide, in which mitochondrial DNA (mtDNA) released by damaged hepatocytes activates neutrophils through binding of Toll‐like receptor 9 (TLR9), further aggravating liver injury. Here, we demonstrated that mtDNA/TLR9 also activates a negative feedback pathway through induction of microRNA‐223 (miR‐223) to limit neutrophil overactivation and liver injury. After injection of APAP in mice, levels of miR‐223, the most abundant miRNAs in neutrophils, were highly elevated in neutrophils. Disruption of the miR‐223 gene exacerbated APAP‐induced hepatic neutrophil infiltration, oxidative stress, and injury and enhanced TLR9 ligand‐mediated activation of proinflammatory mediators in neutrophils. An additional deletion of the intercellular adhesion molecule 1 (ICAM‐1) gene ameliorated APAP‐induced neutrophil infiltration and liver injury in miR‐223 knockout mice. In vitro experiments revealed that miR‐223‐deficient neutrophils were more susceptible to TLR9 agonist‐mediated induction of proinflammatory mediators and nuclear factor kappa B (NF‐κB) signaling, whereas overexpression of miR‐223 attenuated these effects in neutrophils. Moreover, inhibition of TLR9 signaling by either treatment with a TLR9 inhibitor or by disruption of TLR9 gene partially, but significantly, suppressed miR‐223 expression in neutrophils post‐APAP injection. In contrast, activation of TLR9 up‐regulated miR‐223 expression in neutrophils in vivo and in vitro . Mechanistically, activation of TLR9 up‐regulated miR‐223 by enhancing NF‐κB binding on miR‐223 promoter, whereas miR‐223 attenuated TLR9/NF‐κB‐mediated inflammation by targeting IκB kinase α expression. Collectively, up‐regulation of miR‐223 plays a key role in terminating the acute neutrophilic response and is a therapeutic target for treatment of APAP‐induced liver failure. (Hepatology 2017;66:220–234).